2015
DOI: 10.1002/cam4.588
|View full text |Cite
|
Sign up to set email alerts
|

Mus81 knockdown improves chemosensitivity of hepatocellular carcinoma cells by inducing S‐phase arrest and promoting apoptosis through CHK1 pathway

Abstract: As a critical endonuclease in DNA repair, Mus81 is traditionally regarded as a tumor suppressor, but recently correlated with the sensitivity of mitomycin C and 5‐fluorouracil in colon cancer and breast cancer cells. However, its role in chemosensitivity of other human malignancies still remains unknown. This study therefore aims to investigate the effects of Mus81 knockdown on the chemosensitivity of hepatocellular carcinoma (HCC), a usually chemorefractory tumor, and explore the underlying mechanisms. Mus81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…These data suggest that down-regulation of MUS81 could enhance the sensitivity of cisplatin in ovarian cancer cells. Recently, Mus81 was reported to be associated with chemosensitivity in human malignancies such as colon cancer [22], breast cancer [26] and hepatocellular carcinoma [27]. All the data suggest that MUS81 would contribute to chemosensitization.…”
Section: Discussionmentioning
confidence: 98%
“…These data suggest that down-regulation of MUS81 could enhance the sensitivity of cisplatin in ovarian cancer cells. Recently, Mus81 was reported to be associated with chemosensitivity in human malignancies such as colon cancer [22], breast cancer [26] and hepatocellular carcinoma [27]. All the data suggest that MUS81 would contribute to chemosensitization.…”
Section: Discussionmentioning
confidence: 98%
“…The results were consistent with the recent study in HCC cells. 16 These findings suggest that knockdown of Mus81 activates the p53/Bcl-2 pathway to induce cell apoptosis of MCF-7 cells under the treatment of cisplatin. But how the p53/Bcl-2 pathway is activated by knockdown of Mus81, and whether p53/Bcl-2 is downstream of ATM/Chk2 pathway when the MCF-7 cells are treated with cisplatin should be explored by further research.…”
Section: Discussionmentioning
confidence: 86%
“…22 Other studies also indicated that Mus81 was associated with the chemosensitivity in human malignancies such as colon cancer and HCC. 16,34 However, the molecular mechanism is largely unclear. In this study, our results demonstrated that Mus81 knockdown by lentivirus-mediated shRNA could remarkably improve the sensitivity to cisplatin in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations